Elevated serum leptin levels are associated with lower renal function among middle-aged and elderly adults in Taiwan, a community-based, cross-sectional study - Shih, Yu-Lin; Shih, Chin-Chuan; Chen, Sun-Yi-Fan; Chen, Jau-Yuan (Frontiers in Endocrinology, 2022)
Background: Plasma leptin is considered a risk factor for obesity and cardio-metabolic disease, but the link between serum leptin and renal function is still under evaluation. In our study, we focused on the relationship between serum leptin and renal function, and we investigated the relationship in more detail. Methods: The 396 middle-aged and elderly Taiwanese adults recruited for our health survey were the subject of our research. All participants agreed to participate and signed a consent form before they joined and completed our study. We divided the participants into three groups according to eGFR tertiles and analyzed the parameters between each group. Then, we used Pearson’s correlation test to investigate the relationship between eGFR levels and cardio-metabolic risk factors with adjustment for age. The scatter plot indicates the trend between serum leptin levels and eGFR levels. Participants were reclassified into three subgroups according to their leptin levels and the bar chart reveals the prevalence of CKD in each group. Finally, we used multivariate linear regression to evaluate the relationship between serum leptin and eGFR levels with adjustment for age, sex, smoking status, drinking status, BMI, uric acid levels, HTN, DM, and dyslipidemia. Results: In our study, we analyzed the data from 396 eligible participants. A total of 41.4% of the participants were male, and the average age of all participants was 64.81 years (±8.78). The participants in the high eGFR group were more likely to have lower serum leptin levels. Furthermore, eGFR values were negatively correlated with serum leptin levels even after adjustment for age. The prevalence of CKD in the high serum leptin group was higher than that in the low serum leptin group. Serum leptin levels showed significant negative correlations with eGFR levels (β=-0.14, p<0.01) in the multivariate linear regression after adjusting for age, sex, smoking status, drinking status, BMI, uric acid levels, HTN, DM, and dyslipidemia. Conclusion: According to our study, serum leptin levels show a negative relationship with eGFR levels in middle-aged and elderly people in Taiwan. In addition, high serum leptin levels could be an novel marker to survey kidney failure in clinical practices.